2016
DOI: 10.1016/j.jcin.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Fast Computational Approaches to Derive Fractional Flow Reserve From Diagnostic Coronary Angiography

Abstract: The QFR computation improved the diagnostic accuracy of 3-dimensional quantitative coronary angiography-based identification of stenosis significance. The favorable results of cQFR that does not require pharmacologic hyperemia induction bears the potential of a wider adoption of FFR-based lesion assessment through a reduction in procedure time, risk, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
517
3
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 456 publications
(567 citation statements)
references
References 29 publications
10
517
3
2
Order By: Relevance
“…The higher accuracy (92.7%) in FAVOR II China may be explained by the smaller number of lesions with FFR values close to the FFR 0.80 cutpoint. Results in both studies showed improved performance of QFR compared with early validation studies on offline computation of QFR 11, 15. The improved precision may be facilitated by the online analysis setup with instant feedback between operator and analyst.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The higher accuracy (92.7%) in FAVOR II China may be explained by the smaller number of lesions with FFR values close to the FFR 0.80 cutpoint. Results in both studies showed improved performance of QFR compared with early validation studies on offline computation of QFR 11, 15. The improved precision may be facilitated by the online analysis setup with instant feedback between operator and analyst.…”
Section: Discussionmentioning
confidence: 86%
“…The optimal approach was validated in the FAVOR (Functional Assessment by Various Flow Reconstructions) multicenter study, proving that QFR can be computed without pharmacology‐induced hyperemia 11. In FAVOR, QFR was computed post hoc in a core‐lab setting.…”
Section: Introductionmentioning
confidence: 99%
“…The international, multicenter FAVOR pilot study confirmed the good diagnostic performance of QFR and its designated software. 15 Contrast-flow QFR, which is based on the computational hyperemic state and TIMI frame count, had good correlation and agreement with FFR and similar diagnostic accuracy to that achieved using the pharmacologic hyperemic state.…”
mentioning
confidence: 68%
“…The detailed algorithm and theory of QFR computation have been described in a previous report. 15 Examples of reconstructed 3-D QCA and measured QFR are shown in Figure 1D. Lumen diameter pullback and QFR are shown in Figure 1E.…”
Section: Calculation Of Qfrmentioning
confidence: 99%
“…This aim can also be achieved using technology that does not require the use of sensor-equipped guide wires, and even non-invasively. In this context, various efforts have been directed towards the further development of technology that allows calculation of FFR using high fidelity imaging data without the use of a pressure sensor-equipped guide wire in the catheterization laboratory [8][9][10]. For the setting of non-invasive physiological assessment, Yang and Kim [11] summarize current status and future perspectives of computed tomography myocardial perfusion (CTP), focusing on technical considerations, clinical applications, and future research topics.…”
mentioning
confidence: 99%